Eksistensi Kearifan Lokal dalam Simbol-Simbol Suku Dayak Kalimantan Barat - Agnes Ranubaya, Fransesco; Dwi Madyo Utomo, F.X. Kurniawan (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
Local culture and customs contain various ideas, beliefs, perspectives, concepts to bring the community to participate in community life. The development of the times experienced can be an opportunity or also a challenge for cultural communities to continue to explore the seeds of traditional thought that are maintained to this day. Solidarity that is rarely owned by urban people, where everything is different because of the diverse roles. Meanwhile, for traditional communities, the high sense of solidarity and the same conscience are the hallmarks of the cultural richness of the archipelago. Writing scientific papers first discusses the origin of the Dayak tribe, the close relationship between the Dayak people and the real and supernatural world, cultural groupings, community structure, various symbols and reflections. The formulation of the problem of this scientific work is to answer what things are the existence and reflection of local wisdom in the symbols of the West Kalimantan Dayak Tribe. Through this research, it is hoped that it can provide knowledge about the existence of local wisdom in the symbols of the West Kalimantan Dayak Tribe and that all young people can preserve their respective cultural customs reflecting this reflection on the culture of the Dayak Tribe